The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/08853282211063289
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized human amniotic membrane reinforced by MoS2-Polycaprolactone nanofibers, a novel conductive scaffold for cardiac tissue engineering

Abstract: In order to regenerate myocardial tissues with functional characteristics, we need to copy some properties of the myocardium, such as its extracellular matrix and electrical conductivity. In this study, we synthesized nanosheets of Molybdenum disulfide (MoS2), and integrated them into polycaprolactone (PCL) and electrospun on the surface of decellularized human amniotic membrane (DHAM) with the purpose of improving the scaffolds mechanical properties and electrical conductivity. For in vitro studies, we seeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that the incorporation of MoS 2 NPs enhances the conductivity of nylon nanofibers. 29 Given the piezoelectric properties of bone tissue, electroconductive substrates can facilitate the growth and reproduction of bone cells. The utilization of conductive materials in tissue regeneration offers enhanced cell–scaffold interactions, including improved adhesion and proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the incorporation of MoS 2 NPs enhances the conductivity of nylon nanofibers. 29 Given the piezoelectric properties of bone tissue, electroconductive substrates can facilitate the growth and reproduction of bone cells. The utilization of conductive materials in tissue regeneration offers enhanced cell–scaffold interactions, including improved adhesion and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…MoS 2 nanofibers were synthesized using hydrothermal methods and were incorporated into a nylon solution for electrospinning and exhibited a great improvement in conductivity which could enhance cell adhesion and proliferation and also promote cardiac differentiation and maturation of MSCs without the need for additional biochemical supplements. 29…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyocytes cultured of the PPy-PCL scaffold had increased polarization of the gap junction protein connexin-43, with no difference in expression compared to PCL only, as well as improved calcium wave propagation and duration. 128 Other conductive material has also been utilized such as PCL/gelatin with polyaniline (PAni) particles, 131 carbon quantum dots incorporated into PCL during electrospinning, 132 as well as nanosheets of molybdenum disulfide (MoS 2 ), 133 gold nanoparticles, 134 and carbon nanotubes 135 combined with or conjugated to electrospun, fibrous PCL. In all cases, improved electrical conductivity of the scaffold was reported with study-specific results of each study summarized in Table 2.…”
Section: Influence Pcl Propertiesmentioning
confidence: 99%
“…In addition, a similar study showed that PCL-MoS 2 , in combination with photothermal therapy, had bene cial effects on bone regeneration and cell growth [23]. Therefore, we recently designed a hybrid scaffold that contains decellularized human AM and PCL-MoS 2 nanosheets, which showed satisfactory results in cardiac tissue engineering in our previous study [24]. AM/PCL-MoS 2 showed competent mechanical, biocompatible, and electroconductive properties.…”
Section: Introductionmentioning
confidence: 99%